Successful treatment of Class II malocclusion with bidental protrusion using standard edgewise prescription - Mohd Ayaz; Om Prakash Kharbanda (Wolters Kluwer Medknow Publications, 2016)
This case report deals with the successful orthodontic treatment of a 14-year-old female patient having Class II malocclusion with bidental protrusion using standard edgewise prescription. She reported with forwardly placed upper front teeth and difficulty in closing lips. She had prognathic maxilla, retrognathic mandible, and full cusp Class II molar and canine relation bilaterally with overjet of 7 mm. She was in cervical vertebrae maturation indicator Stage IV. The case was treated by fixed extraction mechanotherapy. Interarch Class II mechanics was used to retract the upper incisor and to mesialize the lower molars. Simultaneously, Class I mechanics was used to upright lower incisors. Tip back bend, curve of Spee, and extra palatal root torque were incorporated in upper archwire to maintain molars in upright position and prevent extrusion and deepening of bite, respectively. There was satisfactory improvement in facial profile at the end of 24 months. After a follow-up of 6 months, occlusion was stable.